Distinctive Design Perception: A Case of Toy Packaging Design Determining Children and Parents Purchasing Decision - Wichanat Tiwasing; Nopadon Sahachaisaeree (My University, 2012)
Abstract The present research uses toy packaging as an exploratory case study to test the research design. The case study is so selected since it involves merchandizes in conflict between the needs of children and the trust of guardians. It also engages the role of playing as a learning process promoting the children's imaginary and creativity thinking. Visual stimuli along with self-report questionnaires are used to test the perceptual response of both children and guardians on the aspects of attractiveness, safety, value and taste. The study found a number of contradictions on preferences between children and parents which need design rethinking.
Keywords: Purchasing decision; Consumer Packaging Perceptions and Trends